2021
DOI: 10.1080/03008207.2020.1871475
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of chondrocyte biosynthetic activity by dynamic hydrostatic pressure: the role of TRP channels

Abstract: HistologyAgarose was fixed, dehydrated, processed, embedded in paraffin, and sectioned at 8 µm thickness. Sections were stained with Safranin-O/hematoxylin using standard protocols. Brightfield images were taken at 20X magnification on a VS120 microscope (Olympus). Live Dead imagingConstructs were stained for 30 minutes using the live/dead dye (ThermoFisher, Calcein-AM and Ethidium homodimer-1). Then the samples were imaged using a confocal microscope with the laser powers that were suggested by ThermoFisher.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 74 publications
1
23
0
Order By: Relevance
“…showed that umbilical cord MSC expanded in rotary cell culture system, which creates a combination of simultaneous HP, shear stress and buoyancy force, released approximately 3.8-fold more EVs compared to unstimulated group. [40] The underlying mechanism by which HP regulate stem cell dif- TGF-β production, [27] integrin proteins, [60] intermediate filament, [61] TRP ion channel family, [62] and intracellular calcium stores. [63] A recent review also pointed the possibility of HP affecting primary cilia or nuclei.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…showed that umbilical cord MSC expanded in rotary cell culture system, which creates a combination of simultaneous HP, shear stress and buoyancy force, released approximately 3.8-fold more EVs compared to unstimulated group. [40] The underlying mechanism by which HP regulate stem cell dif- TGF-β production, [27] integrin proteins, [60] intermediate filament, [61] TRP ion channel family, [62] and intracellular calcium stores. [63] A recent review also pointed the possibility of HP affecting primary cilia or nuclei.…”
Section: Discussionmentioning
confidence: 99%
“…The underlying mechanism by which HP regulate stem cell differentiation has not yet been fully elucidated. Previous studies suggest this might happen through HP affecting the endogenous TGF‐β production, [ 27 ] integrin proteins, [ 60 ] intermediate filament, [ 61 ] TRP ion channel family, [ 62 ] and intracellular calcium stores. [ 63 ] A recent review also pointed the possibility of HP affecting primary cilia or nuclei.…”
Section: Discussionmentioning
confidence: 99%
“…TRPV4 activation resulted in an increase in Col-II and sulfated glycosaminoglycans (GAGs) in cartilage. However, chondrocytes with GSK205 in the presence of a mechanical load expressed significantly lower levels of Col-II and higher levels of MMPs ( O'Conor et al, 2014 ; Trompeter et al, 2021a ; Savadipour et al, 2022 ). The effect of TRPV4 activation using GSK101 has been observed to be analogous to that of a mechanical load; chondrocytes treated with GSK101 decrease the synthesis of pro-inflammatory molecules and degradative enzymes ( Fu et al, 2021 ).…”
Section: Chondrocyte Mechanotransduction Mechanismsmentioning
confidence: 97%
“…TRPV4 is a polymodal Ca 2+ permeable non-selective ion channel (Liedtke, 2007), mutations in which leads to a phenotypically diverse range of severe skeletal conditions including lethal metatropic dysplasia, spondylometaphyseal dysoplasia (dwarfirm), and autosomal dominant brachyolmia (Camacho et al, 2010; Nilius & Voets, 2013; Nishimura et al, 2012). First discovered in 2000 (Liedtke et al, 2000; Strotmann et al, 2000), TRPV4 was initially found to be responsible for transducing osmotic signals (Liedtke & Friedman, 2003), but has since been implicated in the cell biosynthetic response to compressive loading (O’Conor et al, 2014), hydrostatic pressure (Savadipour et al, 2022) and oscillatory fluid shear (Corrigan et al, 2018). Previous work has found a critical role for TRPV4 in cartilage and bone cell function in vitro .…”
Section: Introductionmentioning
confidence: 99%